Impact of a pharmacy technician-centered medication reconciliation program on medication discrepancies and implementation of recommendations (Pharmacy Practice, 2017)
Objectives: To evaluate the impact of a pharmacy-technician centered medication reconciliation (PTMR) program by identifying and quantifying medication discrepancies and outcomes of pharmacist medication reconciliation recommendations.Methods: A retrospective chart review was performed on two-hundred patients admitted to the internal medicine teaching services at Cooper University Hospital in Camden, NJ. Patients were selected using a stratified systematic sample approach and were included if they received a pharmacy technician medication history and a pharmacist medication reconciliation at any point during their hospital admission.  Pharmacist identified medication discrepancies were analyzed using descriptive statistics, bivariate analyses. Potential risk factors were identified using multivariate analyses, such as logistic regression and CART.  The priority level of significance was set at 0.05.Results: Three-hundred and sixty-five medication discrepancies were identified out of the 200 included patients. The four most common discrepancies were omission (64.7%), non-formulary omission (16.2%), dose discrepancy (10.1%), and frequency discrepancy (4.1%).  Twenty-two percent of pharmacist recommendations were implemented by the prescriber within 72 hours.Conclusion: A PTMR program with dedicated pharmacy technicians and pharmacists identifies many medication discrepancies at admission and provides opportunities for pharmacist reconciliation recommendations.